2023
DOI: 10.1155/2023/8447804
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Workplace Bullying: Strategies Employed by Nurses in the Healthcare Setting

Ana Lúcia João,
António Portelada

Abstract: Purpose. As regards nursing professionals, workplace bullying is characterized by a set of repeated and banalized negative behaviors carried out by the aggressors that have more power than victims. Such behaviors adversely affect both the victims and the healthcare institutions where the events occur. Upon repeated exposure to workplace bullying, the victims use coping strategies to modify their work environment and adapt to the aggressor, as they try to reduce the discomfort caused by the bullying behavior. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The results of the present study showed that nurses choose more positive bullying management strategies compared to negative ones. These findings are consistent with those of other studies, where positive strategies also scored higher [19,20]. However, studies show that there is great diversity in the bullying coping strategies chosen by nurses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study showed that nurses choose more positive bullying management strategies compared to negative ones. These findings are consistent with those of other studies, where positive strategies also scored higher [19,20]. However, studies show that there is great diversity in the bullying coping strategies chosen by nurses.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of bullying incidents, the reaction of the victim is crucial, especially the reaction of their management. Studies show that nurses use both positive and negative management strategies [18][19][20]. The positive ones include being problem-focused, seeking social support, and having crucial conversations.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of training programs, cognitive rehearsal programs, and educational programs can reduce the impact of bullying on nurses in the workplace [ 95 ]. The need to educate nurses regarding the management of bullying is highlighted by the fact that often nurses choose negative coping strategies, such as avoidance, resorting to substance use, and exhibiting lower levels of acceptance, as their primary coping mechanisms [ 96 ]. When nurses use positive coping strategies and resilience, the impact of bullying on the quality of their work life is mediated [ 32 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coping is characterized by a set of behavioral responses, exhibited by individuals facing stressful situations, which enables them to modify the surrounding environment and adapt to the stress-causing agent, with the intent of reducing discomfort. In this sense, it can be stated that coping allows reducing negative reactions to a given situation [ 33 ], thus acting as a defense mechanism, or, more specifically, as a stable and unconscious mental process used to manage internal and/or external conflicts. Studies indicate high levels of distrust in organisational procedures, which leads to unreported the misconducts (see [ 34 , 35 ]).…”
Section: Background - Wpb In Health Care Facilitiesmentioning
confidence: 99%
“…Studies indicate high levels of distrust in organisational procedures, which leads to unreported the misconducts (see [ 34 , 35 ]). Joao and Portelada [ 33 ] found that among the actions taken by nurses who suffered from workplace bullying (n = 679), the following were most frequently mentioned: telling colleagues (34.2%) what happened, confronting the perpetrator (33.1%), and ignoring the perpetrator (25.1%). 12.6% of nurses stated that they were unable to do anything about the perpetrator or did not feel able to do anything about it.…”
Section: Background - Wpb In Health Care Facilitiesmentioning
confidence: 99%